Re-Examining The Construction Of Unnamed Hire Purchase Contracts For Motor Vehicles And Their Relationship With Leasing - Simbolon, Edison Donauli; Nainggolan, Samuel Dharma Putra; Suryoutomo, Markus; Pakpahan, Elvira Fitriyani; Rahman, Kholilur (Socio Legal and Islamic Law, 2022)
The agreement is the right of every person to enter into an agreement, but entering into an agreement must see the rules or provisions governing the agreement so that the agreement is valid. The lease-purchase agreement is a creation of practice based on the principle of freedom of contract. Freedom of contract is not purely as free as possible, there are limitations in carrying out or making contracts. One of the limitations of the principle of freedom of contract is Article 18 of Law Number 8 of 1999 concerning Consumer Protection, which lists several things that cannot be done in a contract. As a result, if this is done, the contract is null and void by law. Many lease agreements nowadays are agreements made unilaterally by the seller, which should have been made by both parties, what determines everything is that the seller and the consumer just have to agree and comply. This weak consumer position and cause many losses. It is this weak position that is exploited by the seller by imposing several things in the articles of the agreement such as taking back the unit if it does not pay without taking into account the payment made by the consumer beforehand. This research is a normative legal research that uses a statutory approach, a conceptual approach, and case approach that aims to find out the re-examination of motor vehicle lease-purchase agreement construction